PENGARUH MODEL PEMBELAJARAN PEMECAHAN MASALAH VERSI POLYA TERHADAP KEMAMPUAN BERPIKIR RASIONAL PADA MATA PELAJARAN EKONOMI DI SMA KECAMATAN PANYIPATAN - Mirna Mirna (JURNAL SOCIUS, 2019)
AbstractThe research conducted aims to analyze how the economic learning model that has been applied by the teacher and its influence on students' rational thinking skills. Furthermore, how the influence of the learning model emphasizes solving problems with Polya's version of students' rational thinking skills, because previously this model was never used in economic learning. This research was conducted in one of the private high schools in Panyipatan sub-district, namely Abdul Kadir High School. The research method used is quantitative method with quasi-experimental design of pre-test and post-test, the class chosen is class X semester 2 with the subject of inflation. The results of the research and hypothesis testing show that there are significant differences in students' rational thinking abilities taught through the Polya problem solving learning model with students taught with conventional models. Based on the results of the post-test it can be seen that there are differences in mean learning outcomes, where the experimental class has an average value of 74.26, and control class 41.47. This difference is also seen from the results of the two index gain index, where the control class shows a gain index of 0.26 or <0.30 with low criteria. While the experimental class has a gain index of 0.66 with the criteria being. In addition to the gain index, differences in students' rational thinking skills are also seen from the results of different test results (t), from the above calculation, it is obtained thitung = 8.121 while t table = 2.131. So that if it is included in the hypothesis formula, t count> t table, H0 is rejected and H1 is accepted. Based on these results it can be concluded that the ability to think rationally by using the Polya version of problem solving learning model is better or increased than conventional learning models that have been applied in every economic learning, especially in inflation material.Keywords: Polya's version of problem solving learning model, economics, rational thinking.AbstrakPenelitian yang dilakukan bertujuan untuk menganalisis bagaimana model pembelajaran ekonomi yang selama ini diterapkan oleh guru serta pengaruhnya terhadap kemampuan berpikir rasional peserta didik. Selanjutnya bagaimana pengaruh model pembelajaran yang menekankan pada pemecahan masalah dengan versi Polya terhadap kemampuan berpikir rasional peserta didik, karena sebelumnya model ini tidak pernah digunakan dalam pembelajaran ekonomi. Penelitian ini dilakukan di salah satu SMA swasta di kecamatan Panyipatan, yakni SMA Abdul Kadir. Metode penelitian yang digunakan adalah metode kuantitatif dengan kuasi eksperimen desain pre test dan post test, kelas yang dipilih adalah kelas X semester 2 dengan bahasan pokok inflasi. Hasil penelitian dan pengujian hipotesis menunjukkan bahwa terdapat perbedaan yang signifikan dalam kemampuan berpikir rasional peserta didik yang diajar melalui model pembelajaran pemecahan masalah Polya dengan peserta didik yang diajar dengan model konvensional. Berdasarkan hasil post test terlihat adanya perbedaan rerata hasil belajar, dimana kelas eksperimen memiliki nilai rerata 74,26, dan kelas kontrol 41,47. Perbedaan ini juga terlihat dari hasil hitung indeks gain kedua kelas, dimana kelas kontrol menunjukkan indeks gain sebesar 0,26 atau < 0,30 dengan kriteria rendah. Sedangkan kelas ekperimen memiliki indeks gain sebesar 0,66 dengan kriteria sedang. Selain indeks gain, perbedaan kemampuan berpikir rasional peserta didik juga terlihat dari nilai hasil uji beda (t), dari perhitungan di atas didapatkan thitung= 8,121 sedangkan ttabel= 2,131. Sehingga bila dimasukkan pada rumus hipotesis thitung > ttabel, H0 ditolak dan H1 diterima. Berdasarkan hasil ini maka dapat disimpulkan bahwa kemampuan berpikir rasional dengan menggunakan model pembelajaran pemecahan masalah versi Polya lebih baik atau meningkat dari pada model pembelajaran konvensional yang selama ini diterapkan disetiap pembelajaran ekonomi, khususnya pada materi inflasi.Kata kunci: Model pembelajaran pemecahan masalah versi Polya, ekonomi, berpikir rasional